A MIG-15/JNK-1 MAP kinase cascade opposes RPM-1 signaling in synapse formation and learning. - Oliver Crawley; Andrew C Giles; Muriel Desbois; Sudhanva Kashyap; Rayna Birnbaum; Brock Grill (PLoS Genetics, 2017)
The Pam/Highwire/RPM-1 (PHR) proteins are conserved intracellular signaling hubs that regulate synapse formation and axon termination. The C. elegans PHR protein, called RPM-1, acts as a ubiquitin ligase to inhibit the DLK-1 and MLK-1 MAP kinase pathways. We have identified several kinases that are likely to form a new MAP kinase pathway that suppresses synapse formation defects, but not axon termination defects, in the mechanosensory neurons of rpm-1 mutants. This pathway includes: MIG-15 (MAP4K), NSY-1 (MAP3K), JKK-1 (MAP2K) and JNK-1 (MAPK). Transgenic overexpression of kinases in the MIG-15/JNK-1 pathway is sufficient to impair synapse formation in wild-type animals. The MIG-15/JNK-1 pathway functions cell autonomously in the mechanosensory neurons, and these kinases localize to presynaptic terminals providing further evidence of a role in synapse development. Loss of MIG-15/JNK-1 signaling also suppresses defects in habituation to repeated mechanical stimuli in rpm-1 mutants, a behavioral deficit that is likely to arise from impaired glutamatergic synapse formation. Interestingly, habituation results are consistent with the MIG-15/JNK-1 pathway functioning as a parallel opposing pathway to RPM-1. These findings indicate the MIG-15/JNK-1 pathway can restrict both glutamatergic synapse formation and short-term learning.